First report of Faunus ater (Pachychilidae: Gastropod) on the American Continent: A mature empty specimen from Masachapa, Nicaragua, Central America - López S.J., Adolfo (Universidad Estatal a Distancia, Costa Rica, 2012)
Faunus ater (Linné, 1758), es un gastrópodo pachiquílido monotípico deagua salobre, bien conocido en Filipinas y el sudeste asiático. Un únicoejemplar fue hallado en el estuario del río Masachapa, en la costa delPacífico nicaragüense a 60 km de Managua. Este hallazgo constituye unaextensión de ámbito trans-continental, la primera para este género enlas Américas.ABSTRACTFaunus ater (Linné, 1758), a Pachychilid monotypic gastropod, is a wellknown brackish water snail from the Philippines and East Asia. In theyear 1982 a single specimen was found in the estuary section of RiverMasachapa, Masachapa Town, on the Pacific coast of Nicaragua, 60km from Managua. This trans-continental range extension is the firstreported in the Americas.